2004
DOI: 10.1023/b:bebm.0000046928.79653.10
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Homeostasis of the Myocardium in Newborn Albino Rats Exposed to Intrauterine Hypoxia

Abstract: Somatometric indexes were modified in the offspring of rats exposed to hypobaric hypoxia. DNA synthesis and tissue mitotic index increased in 5-day-old male rats, but underwent less pronounced changes in females. Our results indicate that hypoxia modulates morphogenesis of the myocardium. We revealed sex differences in the reaction of newborn albino rats to intrauterine hypoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Some studies [ 19 ] have shown that intermittent or continuous severe hypoxia can lead to an earlier and greater degree of inflammatory response and cell damage in the heart. A previous study suggested that hypoxia can regulate morphological changes and remodeling of the myocardium and can present as wall thickening [ 20 ], suggesting that the thickening of the cardiac wall observed in the patients in this study may not only be the result of the immune response, but that hypoxia may also cause changes in ventricular morphology. Fewer patients presented with right heart enlargement, a thickened right-ventricular wall, and decreased right heart function.…”
Section: Discussionmentioning
confidence: 70%
“…Some studies [ 19 ] have shown that intermittent or continuous severe hypoxia can lead to an earlier and greater degree of inflammatory response and cell damage in the heart. A previous study suggested that hypoxia can regulate morphological changes and remodeling of the myocardium and can present as wall thickening [ 20 ], suggesting that the thickening of the cardiac wall observed in the patients in this study may not only be the result of the immune response, but that hypoxia may also cause changes in ventricular morphology. Fewer patients presented with right heart enlargement, a thickened right-ventricular wall, and decreased right heart function.…”
Section: Discussionmentioning
confidence: 70%